The lived experiences of childhood trauma in war: has post-traumatic growth occurred? - Marzie Hashemi; Maryam Mahmoudzadeh (European Journal of Psychotraumatology)
Background: This study seeks to explore the Post-Traumatic Growth (PTG) condition, a transformative psychological process that promotes improved cognitive functioning and resilience in individuals who suffered childhood trauma, including those affected by the Iran-Iraq war. PTG denotes positive psychological changes, such as enhanced reasoning abilities and emotional strength (Tedeschi, R. G., & Calhoun, L. G. (2004). Posttraumatic growth: Conceptual foundations and empirical evidence. Psychological Inquiry, 15(1), 1–18)).Method: This study views trauma responses as complex and multidimensional, including not only negative outcomes but also coping strategies and psychological growth. Data was collected through semi-structured interviews with 11 participants who witnessed the Iran-Iraq war during childhood. Participants were from a broad spectrum of ethnic backgrounds, reflecting the multiethnic diversity of the war-affected areas. This is significant as their cultural background could affect how they process and heal from trauma due to the multiplicity of values, beliefs, and behaviours. Also, participants' socio-economic backgrounds ranged from low to middle-income, allowing for an investigation of how trauma and growth are impacted by financial resources and constraints. Data were analyzed using Moustakas's phenomenological analysis approach.Results: The findings revealed eight primary and twelve secondary themes ranging from psychological effects and long-term coping mechanisms and wartime recollections. The analysis also revealed distinct patterns of trauma symptoms and growth in adults approaching middle age. The available evidence points to the fact that, although the war-afflicted participants had to contantly live with the lingering effects of trauma across different stages of their lives, they continued to flourish and remain resilient with efficient stress management.Conclusions: The study emphasizes that, in theoretical terms, unexpected developmental steps are crucial, suggesting that childhood trauma, while commonly associated with negative outcomes, can also lead to growth and resilience in certain circumstances.